Pemanfaatan Limbah Plastik Sebagai Paving Block dan Edukasi Dampak Limbah Plastik - Aisita Laila Furqoni; Zakarya Rante Padondan; Muhammad Ryan Syarif Hidayatullah; Zahra Aulia Rizka; Hindun Luthfiyah (Forum Kerjasama Pendidikan Tinggi, 2026)
This Community Service Activity was carried out in Sesumpu Village, which was carried out to solve the problem of Plastic Waste by involving Local Residents and KKN Students of Balikpapan University. The solution to this problem utilizes Paving Blocks as one way to deal with the problem of Plastic Waste, by making it strong and durable to overcome environmental pollution from the plastic waste. In addition to the project carried out, there was a socialization that provided education to residents around Sesumpu Village regarding environmental pollution due to plastic waste and provided the importance of Environmental Law to know the impacts and consequences caused by plastic waste. The results of this activity were an increase in public knowledge and awareness regarding plastic waste management by using Paving Blocks as a form of reducing plastic waste, this provided production results that had economic value. In addition, synergy with the influence of plastic waste that had an impact on environmental pollution by conducting education about environmental law and waste processing training that had a positive impact on changing community behavior in managing plastic waste in order to maintain environmental cleanliness based on Recycling, thus creating a Clean, Healthy and Sustainable Environment.